Relationship marketing and its role in marketing excellence: An exploratory study of the opinions of a sample of managers in four- and five-star hotels in the city of Duhok - Omar, Zakia; Salih, Sami (Humanities Journal of University of Zakho, 2022)
Revenue management considers customer relationship marketing as one of the fixed strategies for many hotels to increase their profitability. Based on that, the research aims to study the role of relationship marketing in marketing excellence in four- and five-star hotels in the city of Duhok, based on a hypothetical scheme that takes into account the direction of the relationship between the dimensions of relationship marketing and marketing excellence. And since relationship marketing has its conceptual roots based on building and sustaining long-term relationships with customers, the research adopted the descriptive analytical approach, and the questionnaire was used to explore the opinions of the sample, which consisted of 50 managers, and some statistical methods were used to analyze the results and test hypotheses, while The most important conclusions of the research indicate the existence of a relationship and a significant impact of relationship marketing on marketing excellence, while one of the most important research proposals was the creation of new services, openness to the latent needs of customers that were not taken into account, as relationship marketing, if used appropriately, will lead to potential and benefits for stakeholders. , including positive verbal recommendations to future customers as a direct result of customer loyalty And greater savings in business costs, all of which can lead to the promotion of marketing excellence and translate into profitability and continuity of the organization.